Multimode memories in atomic ensembles. - Nunn, J; Reim, K; Lee, K; Lorenz, V; Sussman, B; Walmsley, I; Jaksch, D (2008)
The ability to store multiple optical modes in a quantum memory allows for increased efficiency of quantum communication and computation. Here we compute the multimode capacity of a variety of quantum memory protocols based on light storage in ensembles of atoms. We find that adding a controlled inhomogeneous broadening improves this capacity significantly.